1996
DOI: 10.1088/0264-9381/13/5/002
|View full text |Cite
|
Sign up to set email alerts
|

A metric with no symmetries or invariants

Abstract: A metric is given which has no scalar invariants formed from its Riemann tensor or derivatives of its Riemann tensor and which admits, in its general form, no local homotheties or isometries. It is conformally flat and describes pure radiation. Subcases of this metric are the plane wave metric and a metric of Wils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 4 publications
3
62
0
1
Order By: Relevance
“…Using a coordinate transformation w = v/x, Koutras and McIntosh [3] (see also [4]) have recently written this metric in a slightly different coordinate system (u, w, x, y),…”
mentioning
confidence: 99%
“…Using a coordinate transformation w = v/x, Koutras and McIntosh [3] (see also [4]) have recently written this metric in a slightly different coordinate system (u, w, x, y),…”
mentioning
confidence: 99%
“…There is a related result concerning scalar invariants: This result fails in the pseudo-Riemannian setting; Koutras and McIntosh [20] gave examples of non-flat manifolds all of whose scalar Weyl invariants vanish; see also related examples by Pravda, Pravdová, Coley, and Milson [25].…”
Section: Previous Resultsmentioning
confidence: 99%
“…Integrating in the NP formalism, Wils [42] obtained a metric (containing one apparently non-redundant function of one coordinate) which was claimed to represent the whole class of CFPR spacetimes which were not plane waves; subsequently Koutras [23] showed that this was the first metric from which a new essential base coordinate was obtained at third order of the Cartan scalar invariants, which means that its invariant classification formally requires investigation of fourth order Cartan scalar invariants. Koutras and McIntosh [24] have given a slightly more general metric in different coordinates; this form includes plane waves as well as the Wils metric. When Edgar and Ludwig [10], [11], proposed what appeared to be a more general metric (containing three apparently nonredundant functions of one coordinate) to represent all CFPR spacetimes, this provided an ideal opportunity for a non-trivial application of the equivalence problem.…”
Section: Cfpr Spacetimes (Excluding Plane Waves)mentioning
confidence: 99%